BIBLIOMETRIC ANALYSIS OF THE WORLD SCIENTIFIC PRODUCTION IN CHEMICAL ENGINEERING DURING 2000-2011. PART 1: ANALYSIS OF TOTAL SCIENTIFIC PRODUCTION - Ruben Miranda; Esther García-carpintero (Journal of Amasya University the Institute of Sciences and Technology)
A comprehensive bibliometric analysis of Chemical Engineering area has been carried out through the analysis of the scientific production covered in Web of Science during the period 2000-2011. Three complementary studies have been carried out. Part 1 analyzes total scientific production in the area. An important displacement of the scientific production to the Far East has occurred, mainly by the increase in publications from China (the world most productive country since 2008) but also from countries such as India and Iran. Although the share of publications from Europe, and especially from North America, have been decreased significantly, United States is still the country with the highest number of articles among the 1,000 most cited (31.5%), followed by Germany (8.4%) and China (7.5%). Switzerland, Italy, Netherlands, Singapore and Spain outstands as the countries with the highest number of cites per article and year and average impact factors of their publications. The international collaboration in the area is considerably high, especially within European countries (>40% publications are in international collaboration). The scientific production of the area is concentrated in a few journals (top 10 journals publishing around 30% publications and top 25 journals, around 50%) and publishers (Elsevier, Wiley-Blackwell, Taylor & Francis and the American Chemical Society). The countries with the highest number of institutions among the top 100 most productive are China and United States (12 each), followed by France (9), Japan (7) and United Kingdom (7). The top five institutions were from France, China, India, United States and Russia.